2018
DOI: 10.3892/ol.2018.8196
|View full text |Cite
|
Sign up to set email alerts
|

Circulating SH2B1 is associated with an increased risk of gastric cancer

Abstract: Abstract. Gastric cancer (GC) is one of the most common types of cancer in humans and the second leading cause of cancer-associated mortality worldwide. Identifying novel risk factors will facilitate the development of therapeutic strategies to prevent and treat GC. Increased expression of the Src homology 2 B adaptor protein 1 (SH2B1) may stimulate the malignant progression of lung cancer, esophageal cancer and neuroblastoma. However, its function in GC has not yet been investigated. To identify whether incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“… 23 Accumulative evidence have proven that SH2B1 is not only associated with metabolic diseases, such as diabetes, but also with cancer progression. 24 - 28 From the cancer cell line encyclopedia and human protein atlas, SH2B1 was demonstrated to be expressed in the endometrium with higher expression levels in EC; this report is consistent with those of our unpublished study. From the TCGA dataset, the 5-year survival rate of the patients with high SH2B1 expression was 68%, while that of patients with low SH2B1 expression was 80%, suggesting that SH2B1 may have unfavorable influences on the prognosis of patients with EC.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“… 23 Accumulative evidence have proven that SH2B1 is not only associated with metabolic diseases, such as diabetes, but also with cancer progression. 24 - 28 From the cancer cell line encyclopedia and human protein atlas, SH2B1 was demonstrated to be expressed in the endometrium with higher expression levels in EC; this report is consistent with those of our unpublished study. From the TCGA dataset, the 5-year survival rate of the patients with high SH2B1 expression was 68%, while that of patients with low SH2B1 expression was 80%, suggesting that SH2B1 may have unfavorable influences on the prognosis of patients with EC.…”
Section: Resultssupporting
confidence: 90%
“…A series of papers have been published that uncovered the role of SH2B1 in the occurrence, progression, and worsening of colorectal cancer, gastric cancer, and NSCLC. 19 , 27 , 29 In conclusion, we identified a novel biomarker of the EC progression circRNA hsa_circ_0075960, which served as a sponger of miR-361-3p to regulate the expression of SH2B1.…”
Section: Discussionmentioning
confidence: 91%
“…With further exploration of molecular mechanism in present study, we found that BBOX1-AS1 was mainly distributed in the cytoplasm of CRC cells an oncogene in multiple cancers. For example, SH2B1 was identified as a risk factor in gastric cancer and stimulated its progression [24]. SH2B1 enhanced EMT process in lung adenocarcinoma through IRS1/β-catenin axis [25].…”
Section: Discussionmentioning
confidence: 99%
“…SH2B1 was commonly recognized as an oncogene in multiple cancers. For example, SH2B1 was identified as a risk factor in gastric cancer and stimulated its progression [24]. SH2B1 enhanced the EMT process in lung adenocarcinoma through the IRS1/β‐catenin axis [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are several views on this issue. First, it has been confirmed that SH2B1 can regulate cell migration, proliferation and differentiation in vitro [10,17,18], but the mechanism is still unclear. Second, SH2B1 may be involved in the regulation of oxidative stress which can promote the development and progress of many aspects of cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%